EKSISTENSI AGAMA PARMALIM DI DESA AIR KULIM KECAMATAN MANDAU KABUPATEN BENGKALIS - Wahyu sinto; Isjoni Isjoni; bunari bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The Parmalim religion was first introduced by Sisingamangaraja XII in 1907 to the Toba Batak community in Huta Tinggi Village and spread in various regions in the archipelago, one of which is in Riau Province, Bengkalis Regency, Mandau District, Kulim Village. We know that the Toba Batak tribe has a high nomad spirit and a good work ethic in almost all areas of Indonesia where there are settlements of the Toba Batak tribe. Usually the Toba Batak people work as farmers, planters, traders and laborers. The majority of the Toba Batak tribe adheres to Christianity both in their own villages and overseas. Before the entry of Christianity in the Batak Land, it was under the guidance of a German missionary named Nomensen, the Toba Batak tribe. Research objectives (1) To find out the history of the entry of the Parmalim religion into Air Kulim Village. (2) To find out the challenges faced in spreading the Parmalim religion in Air Kulim Village, Mandau District, Bengkalis Regency. (3) To find out the response of the surrounding community to the Parmalim religion in Air Kulim Village, Mandau District, Bengkalis Regency. The method used is the historical method. Research Results Indonesia As a multicultural and multireligious country that is recognized there are 6. but local religions still exist and exist, one of which is in North Sumatra The original religion of the Batak people, namely the Parmalim religion, this religion received discrimination and negative sentiments, especially during the New Order era. few but the Parmalim religion is spread in various regions in Indonesia and is still developing until now, one of which is in Riau, Air Kulim Village, Mandau Regency, Bengkalis Regency. Not against Technological Development. play an active role in the community to support the ideology of Pancasila and the 1945 Constitution. Key Words: The Existence of Parmalim Religion